2004
DOI: 10.1038/nm1094
|View full text |Cite
|
Sign up to set email alerts
|

Defective valves and abnormal mural cell recruitment underlie lymphatic vascular failure in lymphedema distichiasis

Abstract: Lymphatic vessels are essential for the removal of interstitial fluid and prevention of tissue edema. Lymphatic capillaries lack associated mural cells, and collecting lymphatic vessels have valves, which prevent lymph backflow. In lymphedema-distichiasis (LD), lymphatic vessel function fails because of mutations affecting the forkhead transcription factor FOXC2. We report that Foxc2(-/-) mice show abnormal lymphatic vascular patterning, increased pericyte investment of lymphatic vessels, agenesis of valves an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
538
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(563 citation statements)
references
References 49 publications
21
538
1
3
Order By: Relevance
“…Besides the altered endothelial differentiation found in the lymphatic endothelial cells, smooth muscle cells (SMCs) surrounded the JLS which normally only line arteries, veins and large collecting lymph vessels (Petrova et al, 2004;Bekker et al, 2006a). Interestingly, previous research in Foxc2 −/− mice also showed an abnormal amount of SMCs surrounding enlarged lymph vessels (Petrova et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Besides the altered endothelial differentiation found in the lymphatic endothelial cells, smooth muscle cells (SMCs) surrounded the JLS which normally only line arteries, veins and large collecting lymph vessels (Petrova et al, 2004;Bekker et al, 2006a). Interestingly, previous research in Foxc2 −/− mice also showed an abnormal amount of SMCs surrounding enlarged lymph vessels (Petrova et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…This factor is highly expressed in the developing lymphatic vasculature and in the luminal valves in adult lymphatic vessels (Dagenais et al 2004;Petrova et al 2004). Initial development of the lymphatic vasculature proceeds normally in the absence of FOXC2; however, later the patterning of the lymphatic vasculature becomes abnormal.…”
Section: Maturation Of the Lymphatic Vasculaturementioning
confidence: 99%
“…The human disease lymphedema-distichiasis (LD), an autosomal dominant disease, is caused by heterozygousloss-of-function mutations of Foxc2 (Fang et al 2000). Unlike in congenital lymphedema, the lymphatic vasculature in LD is normal or hyperplastic, but there is lymph backXow, presumably due to abnormal lymphatic valves, defective patterning and the presence of ectopic SMCs (Brice et al 2002;Petrova et al 2004). Interestingly, a recent study showed that Foxc2 mutations are associated with primary venous valve failure in both the superWcial and deep veins in the lower limb.…”
Section: Maturation Of the Lymphatic Vasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…Une mutation du gène FOXC2 (16q24), facteur de transcription responsable de la formation des valves et de l'inhibition du recrutement des cellules musculaires lisses ou des péricytes autour des vaisseaux lymphatiques, a été mise en évidence dans cette pathologie. Des manipulations génétiques chez la souris ont confirmé l'effet de cette mutation sur le phénotype [16].…”
Section: Le Lymphoedème Primaire : Fondements Génétiques Et Espoirs Tunclassified